A Meta-analysis of Coefficient Alpha for the Revised Life Orientation Test (LOT-R) - Syahputra, Wahyu; Hayat, Bahrul (FAKULTAS PSIKOLOGI UIN SYARIF HIDAYATULLAH JAKARTA, 2026)
The Revised Life Orientation Test (LOT-R) is one of the most popular instruments for measuring optimism. The authors conducted a meta-analysis, also known as a reliability Generalization study, to estimate the population Cronbach's Alpha for the LOT-R. This study also examined Alpha heterogeneity and identified factors that might influence it. Using a Random Effects Model, the estimated population Cronbach's Alpha based on 211 studies was found to be 0.768 (95% CI: 0.757, 0.778), indicating a good level of reliability. The heterogeneity analysis revealed an I² value of 95.84%, suggesting significant differences among the studies. These differences may stem from factors beyond just methodological variations or population samples. To understand the possible causes for this heterogeneity, a meta-regression analysis was performed, focusing on moderator variables including gender, age, study setting, study type, citation, and language. Among these moderator variables, only the language variable showed a significant impact on the variation in Cronbach's Alpha. In conclusion, the findings suggest that the LOT-R is a reliable instrument for measuring optimism. However, the study also reveals that linguistic factors may influence its reliability, potentially limiting the generalizability of findings across different language groups and in cross-cultural contexts. Therefore, researchers should consider language-related variations when interpreting LOT-R results. Future studies are encouraged to examine further how linguistic differences may affect the instrument's validity and to explore ways to optimize its use across diverse cultural settings.